What Do Israeli Osteoporotic Men Know and Do about Their Disease? - Offer Emanuel Edelstein (Journal of Osteoporosis)
Aims. The aims of the current study were to evaluate the level of knowledge about osteoporosis among osteoporotic men and to assess the correlations with their health behaviors. Method. A convenience sample of 100 osteoporotic men (mean age 63) attending the bone and mineral clinic at a major medical center in Israel was recruited in 2004. Participants were interviewed by phone using an adapted version of the Facts on Osteoporosis Quiz (FOOQ). Participants were also asked to report on their daily calcium intake and participation in physical activities. Results. The overall level of knowledge about the disease demonstrated by the participants was moderate. Higher education, older age, and fewer fractures were correlated with a higher level of knowledge. In addition, higher levels of education and knowledge were correlated with higher calcium intake. Lastly, a higher knowledge level, older age, and fewer fractures were correlated with higher participation in physical activities. Conclusions. Given the correlations between health behaviors and the level of knowledge among osteoporotic men, intervention programs should be used to evaluate and improve knowledge about osteoporosis, especially among less educated patients.